Pengembangan Aplikasi Klasifikasi Gambar Foto Kegiatan ‘Remaja Bagi Kristus’ Gereja Isa Almasih Kega - Siahaan, Leonardo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
This study aims to develop an image classification application based on a website. An application will be made to be able to classify pictures of activities at Youth For Christ, KEGA Isa Almasih Church. In this study using the CNN (Convolutional Neural Network) method to create a model. The machine learning model used in building this application uses the Tensorflow software library. The software development method used is the incremental method. The dataset used in this study was collected as much as 600 image data and will be divided into 3 data variables, namely praying, preaching, and worship. The result of the application that is built is a simple website-based image classification application so that users can easily use the application. By utilizing the HTML programming language in making application interfaces and Python as a programming language in creating machine learning models used in applications, in making this application the researcher also uses Flask as a backend for the application.